Analysis of the quality of employment in Paraguay - Julio Fernández Frutos (Población y Desarrollo, 2015)
In 2013 the United Nations Programme for Development based in Paraguay disseminated the National Human Development Report: Decent Work and Human Development (INDH DWHD 2013). That report contains data up to 2011 and demonstrated the close link between the level of human development and quality of employment at national and departmental levels. One of the major difficulties of the report was to find an indicator to measure decent work (TD DW). The complexity of the concept made it difficult to find an indicator to operationalize measurement. The contribution of this study: Analysis of Quality of Employment in Paraguay is manifold: first update information to date on the latest survey of households released (2014) and on the other hand, explores aspects not considered in the 2013 INDH DWHD such as the analysis of IQW branches of economic activity and deepens other aspects such as the quality of employment in the public sector versus the private sector and department.